Prevalence of an incompetent lip seal during growth periods throughout Japan: a large-scale, survey-based, cross-sectional study - Yukiko Nogami; Issei Saitoh; Emi Inada; Daisuke Murakami; Yoko Iwase; Naoko Kubota; Yuki Nakamura; Masami Kimi; Haruaki Hayasaki; Youichi Yamasaki; Yasutaka Kaihara (Komiyama Printing Co. Ltd, 2021)
Abstract Background Systemic and local factors may lead to disruption of craniofacial growth and development, causing an imbalance between the orofacial skeleton, muscle and soft tissue, dental occlusion, and the dental arch during growth periods. We aimed to reveal whether the prevalence of incompetent lip seal (ILS) varies with age and region, as well as to clarify the factors related to an ILS, in a national, large-scale epidemiological study. Methods We surveyed 3399 children, from 3 to 12 years of age, visiting 66 pediatric dental clinics throughout Japan. For this survey, we employed a questionnaire consisting of 44 questions regarding daily health conditions and lifestyle habits. We evaluated the differences in ILS prevalence by age and region (using a Cochran-Armitage test for trend and a Kruskal-Wallis test), and the relationship between ILS and factors investigated in the questionnaire (using Spearman's rank correlation coefficient). Results We observed that 30.7% of Japanese children exhibited an ILS and that the ILS rate increased with age (p < 0.001). There were no regional differences in the rate of ILS in Japanese children (p = 0.506). We revealed that 12 of 44 survey items exhibited a statistically significant correlation with ILS (p < 0.001), using Spearman's rank correlation coefficient. These items involved orofacial morphology, mouth breathing, and possibly, allergic rhinitis. Conclusion The rate of ILS seems to increase with age in children, throughout Japan. Therefore, this disorder may not self-correct during the growth periods in these children. Guidelines are required for pediatric dentists to recognize ILS among children aged 3-12 years.